(untitled) (Fiep Bulletin - online, 2012)
The present study sought to evaluate the quality of life of visually impaired adults through the WHOQOL-bref instrument. It also sought to identify aging group, gender, and nature of impairment, as well as being acquainted with the reasons for the practice of physical activities and the importance given to it. The sample covers 14 subjects who attend an association for the visually impaired in a city in Vale do Sinos/RS area. For the analysis of the data the use of descriptive statistics was done through the absolute (n) and relative (%) frequency contributions, minimum and maximum values, arithmetical means, and standard deviation. The results found in the research characterize the sample as ranging in age from 22 to 74 years old (average = 49,3 ± 13,4 years old), represented as 71,4% male and 28,6% female; married 42,9%, single 35,7%; 71,4% blind people and 28,6% low sighted; 71,4% of acquired impairment and 28,6% congenital impairment; retinal detachment, glaucoma, retinal infection and retinal burn, respectively represented with 14,3%. The other cases, equally distributed in 7,1%, were: degenerative related to aging, cataract, fall and diabetes. It was observed that in the results related to Quality of Life there is a predominance of the psychological domain with 71,4%, followed by the social domain with 66,1%, the physical and environmental domains with 63,5% and 58,5% respectively. Considering the exposed results in comparison with the averages related to gender, it is observed that women show better results in physical domain in relation to men. Regarding the variables aging group, type of impairment, and practice of physical activities there are no significant differences. Facing the results, it is observed that the Quality of Life of the study subjects was rated as good, a fact that may be related to the context in where the visually impaired is inserted, for they effectively participate of several activities provided by the association they attend.